Growth differentiation factor 15 (GDF15) elevation in children with newly diagnosed cancer - Runco, Daniel V.; DiMeglio, Linda A.; Vanderpool, Charles P.; Han, Yan; Daggy, Joanne; Kelley, Mary M.; Mikesell, Raya; Zimmers, Teresa A. (Frontiers in Oncology, 2023)
Background: Growth differentiation factor 15 (GDF15), an inflammatory marker and mediator of adult cancer cachexia, remains largely unexplored in children. GDF15 increases nausea, vomiting, and anorexia, in cancer and contributes to malnutrition, with the potential to be a cachexia therapeutic target. No studies have examined GDF15 in children with newly diagnosed cancer. Our pilot study compares GDF15 in children with newly diagnosed cancer to age- and sex-matched controls and correlates levels with anthropometric measurements and quality-of-life (QOL). Methods: Children with newly diagnosed cancer, ages 2-21 years were enrolled with serum GDF15 ELISA, anthropometric measures (height, weight, and mid-upper arm circumference (MUAC)) and QOL assessments (using PedsQL™ Core and Gastrointestinal Modules) collected at baseline and repeated 3 months later. Serum GDF15 levels were obtained from age- and sex-matched controls for comparison. Results: Fifty-seven participants enrolled (N=30, cancer group; N=27, control group) with median age of 8.8 years (IQR 5.6-15.9 years). Participants were primarily male (54.4%), white (82.5%), and non-Hispanic (82.5%). Cancer diagnoses included acute lymphoblastic leukemia (N=8), lymphoma (N=8), neuroblastoma (N=5), soft-tissue tumors (N=4), acute myeloid leukemia (N=2), and single participants with brain, kidney, and bone tumors. Baseline GDF15 was higher in cancer compared to control cohort (median=614.6pg/mL and 320.5pg/mL, respectively; p<0.001). When examining participants with evaluable baseline and 3-month follow-up GDF15 levels (N=18), GDF15 was not statistically different (median=657.1pg/mL and 675.3pg/mL, respectively; p=0.702). Thirteen of the 30 participants and 21 caregivers completed the PedsQL™ Core and Gastrointestinal symptom modules. QOL scores did not differ significantly at 3-month follow-up compared to baseline, but diarrhea worsened (p=0.017). Median participant response for diarrhea at baseline was 92.9 (IQR=92.9-96.4; N=13) which was significantly better than follow up (median=78.6; IQR= 71.4-92.9; p=0.017). There were no correlations between change in height, weight, or MUAC and change in GDF15 levels (p=0.351, 0.920, and 0.269 respectively). Discussion: GDF15 is elevated in children with cancer at diagnosis compared to controls but did not correlate to anthropometric measurements or QOL. This pilot study will inform future prospective studies to better describe the natural history of GDF15, as well as role in cachexia and a potential therapeutic target.